XÂY DỰNG QUY TRÌNH TỔNG HỢP PYRIDOSTIGMIN BROMUA DÙNG TRONG PHÒNG CHỐNG NHIỄM ĐỘC THẦN KINH CƠ PHOSPHO - Nguyễn, Công Tỉnh; Hoàng, Quang Cường; Lê, Thị Huệ (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
SYNTHESIS OF PYRIDOSTIGMINE BROMIDE USED IN PREVENTION OF ORGANOPHOSPHATE NERVE AGENTS POISONINGPyridostigmine, a quaternary carbamate inhibitor of acetylcholinesterase, is used to treat muscle weakness with myasthenia gravis or to reduce the effects of curariforms drug toxicity. Pyridostigmine bromide have been approved for military use as an agent for the protection of cholinesterase enzymes (against soman and tabun exposure). In this paper, we described the synthesis of pyridostigmine bromide from pyridin-3-yl-dimethylcarbamate. The highest yield (75.68%) was obtained using following reactional conditions: 25°C, 14h and the molar ratio of pyridine-3-yl-dimethylcarbamate:methyl bromide=1:1,2. HPLC analysis of synthetic pyridostigmine bromide showed a purity of 99.3%. This simple and efficient method can be used to scale up for the synthesis of pyridostigmine bromide as raw material in the production of myasthenic gravis drugs, as well as anti-nerve agent drugs in Vietnam.